Notables, merchants, and shaykhs of Southern Iran and its ports - Ricks, Thomas M. (Piscataway, NJ)
xxii, 318 sayfa
Keywords: “This book investigates the socio-cultural and maritime history of 18th century – early 19th-century Southern Iran and the Persian Gulf in terms of the merchants, mariners and captains who lived and died in the turbulent waters of the western Indian Ocean. This “uncertain frontier” between a revitalized Ottoman Empire to the west and an emergant British India to the east became a testing grounds for the communities of the Gulf. Generally assumed to be a period of anarchy, the 18th-century maritime peoples resolved differences by marriage, forged alliances, and adapted their mercantile skills to the emerging age of global power“ -- Yayıncı.